2012
DOI: 10.1111/j.1476-5381.2012.01906.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of PARP to endothelial dysfunction and hypertension in a rat model of pre‐eclampsia

Abstract: BACKGROUND AND PURPOSEUnder conditions of increased oxidative stress, such as pre-eclampsia and diabetes, overstimulation of PARP leads to endothelial dysfunction. Inhibition of PARP has been demonstrated to reverse the vascular dysfunction associated with diabetes in vivo. The present study was carried out to investigate the role of PARP in mediating the endothelial dysfunction associated with pre-eclampsia. EXPERIMENTAL APPROACHUteroplacental perfusion was surgically reduced in pregnant rats to produce the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Consistent with human studies, in the rat RUPP model, vessels from normal‐pregnant animals show impaired endothelium‐dependent vasodilatation following incubation with RUPP plasma . Experiments in both humans and rats have found that plasma‐mediated endothelial dysfunction is prevented by incubating vessels in the presence of a PARP inhibitor, suggesting a role for vascular dysfunction mediated by oxidative stress‐stimulated PARP activation .…”
Section: Placental Ischemiasupporting
confidence: 67%
“…Consistent with human studies, in the rat RUPP model, vessels from normal‐pregnant animals show impaired endothelium‐dependent vasodilatation following incubation with RUPP plasma . Experiments in both humans and rats have found that plasma‐mediated endothelial dysfunction is prevented by incubating vessels in the presence of a PARP inhibitor, suggesting a role for vascular dysfunction mediated by oxidative stress‐stimulated PARP activation .…”
Section: Placental Ischemiasupporting
confidence: 67%
“…The most significant amelioration was seen on MAP, RBF and renal oxygen metabolism. It is reported that suppression of PARP could influence both vascular and hemodynamic function [15,25] by upregulating the CO, attenuating cardiomyocyte dysfunction and reducing the SVR [26,27,28]. Hans et al [29] presented that PARP-1 gene deletions prominently prevent the faltering of hemodynamic parameters in cardiac hypertrophy by directly effecting MMP-9 and TIMP-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In states of increased oxidative stress, such as diabetes, overstimulation of PARP leads to endothelial dysfunction and PARP inhibitors have been shown to be of benefit [62]. A recent investigation has demonstrated a protective effect of a PARP inhibitor, preventing the development of both endothelial dysfunction and hypertension, in a rat model of preeclampsia [62].…”
Section: Novel Therapeutic Targets and Emerging Treatmentsmentioning
confidence: 99%
“…A recent investigation has demonstrated a protective effect of a PARP inhibitor, preventing the development of both endothelial dysfunction and hypertension, in a rat model of preeclampsia [62]. …”
Section: Novel Therapeutic Targets and Emerging Treatmentsmentioning
confidence: 99%